2017
DOI: 10.3233/jbr-170156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression of β-actin, RuANS and RuMYB10 genes involved in the biosynthesis of anthocyanin using RT-qPCR in Rubus niveus in the Rumiñahui Canton

Abstract: Abstract.BACKGROUND: Berries such as Rubus has caught the attention of scientists and consumers because of their nutritional quality. Furthermore, the presence of phenolic compounds specifically anthocyanins have added potential of antiaging, anticarcinogenic and antioxidant properties to the fruit. Gene expression studies have demonstrated the importance of flavonoids and their biosynthetic pathways, further increasing the research interests alternative and natural sources for these compounds. OBJECTIVE: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The standard curve in acceptable parameters presents an efficiency of 1,922 and an error close to 0, providing certainty in the tests [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard curve in acceptable parameters presents an efficiency of 1,922 and an error close to 0, providing certainty in the tests [13].…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the reference values, logarithmic serial solutions of the complementary DNA obtained previously were prepared, the samples were quantified in the Qubit® 2.0 Fluorometer, with Qubit® dsDNA HS Assay Kit (Life) [13].…”
Section: Standard Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the accuracy of RT-qPCR results being easily affected by sample difference, tissue specificity, extracted RNA quality, and other factors, the expression analysis of genes requires normalization to reference genes [ 14 ]. Several studies have shown that the β-actin and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) were selected as the RT-qPCR internal reference genes in Rubus niveus and Rubus idaeus , respectively [ 15 , 16 ]. However, studies on the reference genes of Rubus have not been systematically reported.…”
Section: Discussionmentioning
confidence: 99%
“…The amplification protocol was programmed in the Light cycler 4.0 software (Roche): initial denaturation at 95 °C, for 1 cycle, then 60 denaturation cycles at 95 °C, hybridization at 60 °C and extension at 72 °C, to finally reach the last step of cooling for 1 cycle at a temperature of 40 °C. Finally, the previously saved external standard curve must be imported to obtain the quantitative data 16 .…”
Section: Quantification In Rt-qpcrmentioning
confidence: 99%